Multicenter laparoscopic evaluation of the peritoneum in peritoneal dialysis patients. Issue 2 (17th March 2020) - Hara, Kazuaki; Io, Hiroaki; Wakabayashi, Keiichi; Maeda, Takuya; Kanda, Reo; Nakata, Junichiro; Maeda, Kunimi; Sengoku, Hironobu; Machida, Michio; Kojima, Kuniaki; Sakamoto, Kazuhiro; Tomino, Yasuhiko; et al.
Abstract: Laparoscopic findings have been used to confirm peritoneal degenerations in peritoneal dialysis (PD) therapy. This study evaluated morphological changes in the peritoneum and their clinical relevance in patients undergoing PD. Laparoscopic findings at the rectovesical peritoneum were evaluated and scored using an imaging system at the time of PD catheter removal in this multicenter study. Angiogenesis evaluated by the vascular score (VS), color changes score (CCS), plaque score (PS), PD duration, history of peritonitis, dialysate/plasma creatinine (D/P Cr) levels, and age at PD termination were statistically analyzed. The VS of patients with PD duration more than 96 months was significantly decreased compared with that of the other patients and was negatively correlated with D/P Cr levels at PD termination. The CCS for patients with PD duration more than 96 months were significantly higher than those for the other patients and positively correlated with D/P Cr levels at PD termination. The PS of patients with recurring peritonitis were significantly higher than those of the other patients. Diminished vascularity and increased color changes in the peritoneum may be predictive of D/P Cr levels with peritoneal degradation. Laparoscopic evaluation of the abdominal cavity can provide detailed information about peritoneal injury.